A Cardiac Amyloidosis Presentation: Atrial Mass Versus Thrombus - Nanda, Saheba (Cureus, 2020)
Cardiac neoplasms are a rare finding of which a cardiac myxoma is the most commonly encountered. Therefore, a density identified in the left atrium commonly leads to the presumptive diagnosis of an atrial myxoma. However, other pathologies, such as atrial thrombi, can mimic in clinical presentation and appearance to a myxoma. Clinically, these pathologies may lead to obstructive symptoms such as syncope, palpitations, or sudden cardiac death. At present, echocardiography, magnetic resonance imaging, or computed tomography can be used to identify such masses, but fall short of identifying the primary cause. The management of atrial thrombi is not yet fully understood and definite recommendations have not been established. We present a case of an 87-year-old man complaining of syncopal episodes found to be secondary to an incidental intracardiac density resulting from age-related amyloidosis.